Editorial of the First Edition Journal of Sylva Indonesiana - Slamet, Bejo; Nuryawan, Arif (Journal of Sylva Indonesiana, 2018)
This editorial is an opening remark of the first edition Journal of Sylva Indonesiana (JSI) containing the growth and development of the journal managed by Faculty of Forestry Universitas Sumatera Utara (â€œFahutan USUâ€). In the first stage, â€œJurnal Ilmiah Pertanian Kulturaâ€ published by Faculty of Agriculture USU has been targeted by faculty member of â€œFahutan USUâ€ for dissemination of their research results. This journal has been accredited by Directorate General of Higher Education in 2003 consequently its scope become specific, forestry science did not include therein. Hence, at that time, Program Study of Forestry Science under management of Faculty of Agriculture USU initiated the issuing of Peronema Forestry Science Journal in 2005 in order to accommodate scope of forestry science. Unfortunately the service and production of this journal become stagnant because most of the editorial staff pursued higher education in outside Medan city and the funding for publishing and printing vanished. In 2012, with the new spirit, Program of Forestry Science re-issued the new journal called â€œForestaâ€ Indonesian Journal of Forestry. It was a pity, the production process of this journal discontinued regarding to no submission of the manuscripts. All of the research results of undergraduate students of Program Study of Forestry Science have been uploaded into Peronema Forestry Science Journal in online version since 2014. In connection with establishment of organization structure of Faculty of Forestry completely, the publishing of JSI has been started in 2018 even though the editorial works of this journal has been begin since 2017, comprise call of paper, blind-review process, correspondence with the authors, layout and editing, including upload in the journal website. Supply of the manuscripts is provided not only from undergraduate research results of Faculty of Forestryâ€™s students but also from the outside. With the commitment of the funding from the Faculty of Forestry USU, hopefully JSI can reach the target as the national accredited journal and it can achieve the status to be a reputation journal in the field of forestry in the future.